(untitled) (Research, Society and Development, 2021)
Introduction: Chiari malformation is the herniation of the cerebellar tissue through the foramen magnum, which can lead to a series of signs and symptoms that can qualitatively affect the life of the person with this syndrome. Because they have many symptoms, they can lead to incorrect diagnosis and treatment if there is not adequate knowledge. Objective: this study aims to correlate the orofacial clinical findings in patients with Chiari malformation and its differential diagnosis with TMD. Methodology: A literary review was carried out by crossing the selected descriptors in electronic search, found in the journals of the databases SCIELO, LILACS, SCOPUS and MEDLINE. Discussion: Chiari Malformation presents a group of congenital malformations that directly affect patients’ quality of life. This condition may be associated with trigeminal neuralgia, but its exact mechanism is still not clearly understood. Magnetic resonance imaging is the gold standard imaging test for the diagnosis of this condition and the choice for the ideal therapy, both clinical and surgical management, should be correctly indicated in symptomatic patients, due to the chance, although rare, of possible spontaneous or complete resolution of tonsillar herniation. Conclusion: The clinical manifestations of Chiari Malformation are variable, and may present similarities and even be confused with other conditions of the stomatognathic system such as TMD. Thus, knowledge about its clinical manifestations is important, so that it can be correctly diagnosed and better treated.